2015
DOI: 10.1097/hjh.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of renal transplant patients with true resistant hypertension

Abstract: The present study provides evidence about the prevalence of true resistant hypertension in renal-transplant patients. It also shows the very high cardiovascular risk of true resistant hypertension and the elevated association of this condition with renal failure, organ damage, and history of cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In our data, 24.1% of patients were considered to have white‐coat HTN. This is nearly in agreement with previous studies where white‐coat effect was present in 20% to 40% . The concordance rates between office BP and ABPM change according to the studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our data, 24.1% of patients were considered to have white‐coat HTN. This is nearly in agreement with previous studies where white‐coat effect was present in 20% to 40% . The concordance rates between office BP and ABPM change according to the studies.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 67.8% of patients were classified as nondippers. In many previous studies, nondipping pattern was reported to be between 25% and 90% . Loss of normal diurnal BP variation, which has been described to occur among patients with chronic kidney disease, has been associated with a greater rate of CVD events as well as progression of renal disease .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The presence of an atherosclerotic RAS, even a less than 50% stenosis, is accompanied by a high risk of cardiovascular complications as compared to hypertension without RAS (8, 13, 1618). A cohort of patients with RAS, detected at the time of coronary angiography, showed a 4-year survival rate of 65% as opposed to 86% for those without RAS (16).…”
Section: Discussionmentioning
confidence: 99%